Engineering methods and tools for software safety and security - Broy, M., 1949-; Sitou, Wassiou; Hoare, C. A. R. (Charles Antony Richard), 1934- (NATO science for peace and security series. Information and communication security, 2009)
Based on the specific needs in applications of software technology, models and formal methods must serve the needs and the quality of advanced software engineering methods. This book provides a presentation of topics on how to meet such challenges covering both theoretical foundations and industrial practice.